Optimization Matrix Formulas Using Hypromellose and Carboxymethylcellulose Sodium for Metformin HCl Extended Release Caplets - Andrie, Agus; Kurniawan Syah, Insan Sunan; Chaerunisaa, Anis Yohana (Universitas Padjadjaran (Unpad), 2023)
The first-line pharmacological therapy in type II diabetes patients in people who are overweight and have normal kidney function is metformin. However, metformin with immediate release has been found to have some weaknesses, namely that a maximum dose of 2,000 mg/day requires use 2 to 3 times a day, which leads to a potential patient's non-compliance, in addition to causing disorders in the intestinal tract. To overcome this problem, a formulation was developed that was modified with extended release using the direct compressed method. This study aims to determine the influence of variations in the concentration of hypromellose and carboxymethylcellulose natrium (Na-CMC) matrices in the extended-release of metformin HCl 500 mg to obtain an optimal and similar extended-release system capsule formula to the originator drug, as well as to prove the quality of the selected formula through stability monitoring. This research is expected to produce the optimum formula for metformin HCl capsules extended release and can be applied in the pharmaceutical industry into commercial products.Keywords: Diabetes, Metformin HCl, Extended release, Direct compressed, Hypromellose, Carboxymethylcellulose natrium.